The Christian family guarantees management of the value of human life - Mohor-Obreja, Bogdan (Technium Social Sciences Journal, 2023)
The Orthodox Church has always taught that human life begins at conception when a sperm fuses with an egg to produce a living, genetically unique being. Just as the Church takes special care of helpless and defenseless human beings, so much more does she take care of human embryos and unborn babies, that is, helpless beings. By accepting and legislating the artificial interruption of pregnancy, paradoxically, hospitals and maternity hospitals, places meant to protect and give life, became cemeteries for those who were to see the light of day.